Hydroxyethyl starch versus saline for resuscitation of patients in intensive care: long-term outcomes and cost-effectiveness analysis of a cohort from CHEST. Issue 10 (October 2016) - Taylor, Colman; Thompson, Kelly; Finfer, Simon; Higgins, Alisa; Jan, Stephen; Li, Qiang; Liu, Bette; Myburgh, John; ,
Summary: Background: Hydroxyethyl starch for fluid resuscitation in critically ill patients is not associated with improved short-term patient-centred outcomes compared with crystalloid fluid solutions. However, its effect on longer term health economic outcomes has not been reported. Methods: We did a prespecified cost-effectiveness analysis of a cohort of patients from New South Wales enrolled in the Crystalloid versus Hydroxyethyl Starch Trial (CHEST), who were randomised to treatment with either 6% hydroxyethyl starch with a molecular weight of 130 kD and a molar substitution ratio of 0·4 or 0·9% sodium chloride (saline) for fluid resuscitation. Clinical outcomes were mortality and life-years gained at 6 months and 24 months, health-related quality of life at 6 months, and quality-adjusted life-years gained at 6 months. Health economic outcomes were hospital and intensive-care unit (ICU) resource use and costs at 24 months and cost-effectiveness, which we defined as the probability of reaching a willingness-to-pay threshold of less than A$50 000 per quality-adjusted life-year gained at 6 months and $100 000 per life-year gained at 24 months. CHEST is registered withClinicalTrials.gov, numberNCT00935168 . Findings: 3537 (51%) of 7000 patients were enrolled into CHEST from New South Wales, of whom 3450 (98%) were included in our cost-effectiveness analysis. Mortality at both 6 months and 24 months did not differ between the hydroxyethyl starch and saline groups (6 months: 397/1684 [24%] vs 382/1706 [22%]; relative risk [RR] 1·05, 95% CI 0·93–1·19; p=0·41; 24 months: 586/1687 [35%] vs 594/1708 [35%]; RR 1·00, 95% CI 0·91–1·10; p=0·89). The mean number of life-years gained at 6 months and 24 months was similar between the hydroxyethyl starch and saline groups (6 months: 0·41 days [SD 0·18] vs 0·41 days [0·17]; p=0·25; 24 months: 1·46 years [SD 0·80] vs 1·47 years [0·79]; p=0·72). At 6 months, the mean health-related quality of life score was 0·67 (SD 0·34) with hydroxyethyl starch versus 0·69 (0·35) with saline (p=0·33). The mean number of quality-adjusted life-years gained did not differ between the hydroxyethyl starch and saline groups at 6 months (0·26 days [SD 0·18] vs 0·26 days [0·18]; p=0·33). Total hospital costs (including ICU costs) at 24 months were similar between the hydroxyethyl starch and saline groups (A$62 196 [55 935] vs $62 617 [56 452]; p=0·83). The probability that hydroxyethyl starch was cost effective was 11% at 6 months and 29% at 24 months. Interpretation: Although longer term clinical outcomes did not differ between patients resuscitated with hydroxyethyl starch or saline in the ICU, from a health-care payer's perspective, the probability that hydroxyethyl starch is cost effective in these patients is low. Funding: Division of Critical Care and Trauma, George Institute for Global Health.